2018
DOI: 10.5194/cp-14-577-2018
|View full text |Cite
|
Sign up to set email alerts
|

Timescale dependence of the relationship between the East Asian summer monsoon strength and precipitation over eastern China in the last millennium

Abstract: Abstract. Precipitation/humidity proxies are widely used to reconstruct the historical East Asian summer monsoon (EASM) variations based on the assumption that summer precipitation over eastern China is closely and stably linked to the strength of EASM. However, whether the observed EASM–precipitation relationship (e.g., increased precipitation with a stronger EASM) was stable throughout the past remains unclear. In this study, we used model outputs from the Paleoclimate Modelling Intercomparison Project Phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…There are six megadroughts (marked in gray) in the reconstruction data (Figure 1a), while there are five megadroughts in the control run (Figure 1b) and 3-6 megadroughts in the forced runs (Figure 1c-g). Previous studies [45] have shown that CESM broadly reproduces the observed EASM and EASM-precipitation relationship with some small biases. Recall a megadrought event is defined as a period with precipitation anomalies less than zero for at least 20 consecutive years, and those drought events that do not persist for 20 years are not considered megadrought events in this study.…”
Section: Simulated Megadroughtsmentioning
confidence: 62%
“…There are six megadroughts (marked in gray) in the reconstruction data (Figure 1a), while there are five megadroughts in the control run (Figure 1b) and 3-6 megadroughts in the forced runs (Figure 1c-g). Previous studies [45] have shown that CESM broadly reproduces the observed EASM and EASM-precipitation relationship with some small biases. Recall a megadrought event is defined as a period with precipitation anomalies less than zero for at least 20 consecutive years, and those drought events that do not persist for 20 years are not considered megadrought events in this study.…”
Section: Simulated Megadroughtsmentioning
confidence: 62%
“…Moreover, it did not show a significant downtrend as most models did (Figure 5b). This could be related to the inadequacy of CSIRO-Mk3L-1-2 in reproducing the modern East Asian summer monsoon (Shi et al, 2018), which is a key system for precipitation over China. Second, GISS-E2-R-p121 showed a large downtrend, which was at least double the magnitude of the other models (Figure 5c) and might be linked to its cooling drift (Coats et al, 2015a).…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al . () also found that the nonstationary decadal EASM‐precipitation relationship may be attributed to the internal variability of the climate system. Previous studies (Li et al ., ; Yang et al ., ; Li and Wang, ) indicated that the spatial pattern of annual precipitation anomalies over the eastern China and EASM anomalies are closely associated with the decadal Pacific SST pattern, such as the PDO (Ma, ; Zhang and Zhou, ) For example, Yang et al .…”
Section: Introductionmentioning
confidence: 89%